Characterization of annulus fibrosus lesions on magnetic resonance imaging in dogs affected by intervertebral disc disease, a descriptive case series - Merbl, Yael; Kaur, Sukhmeen; Kei, Tiffany G.; Ryan, Elle; Johnson, Philippa J. (Frontiers in Veterinary Science, 2024)
ObjectiveDescribe and characterize the magnetic resonance imaging (MRI) appearance of annulus fibrosus (AF) high-intensity zone (HIZ) in dogs suffering from intervertebral disc disease (IVDD).MethodsA single-center retrospective case series study. Databases were reviewed from 2011 to 2022 for dogs that underwent MRI diagnosis due to suspected IVDD. Cases were included if they had T2-weighted (T2W) hyperintense annular fibrosus lesions (AFL) on the imaging diagnosis report. To be included, the MRI scan had to be of diagnostic quality and include a sagittal T2W, proton density (PD), or short tau inversion recovery (STIR) sequence of the annular lesion, together with transverse T2W and/or dorsal plane STIR sequences over the HIZ region.ResultsForty one cases (in 39 dogs) of HIZ were included in the study. Mixed breed dogs were the highest represented group representing 25.6% of the cohort. Patient median age was 7.5 years and median weight 23 kg. Primary HIZ appeared in 7/39 dogs (17.95%) and the remaining had acute non-compressive nucleus pulposus extrusion (ANNPE), hydrated nucleus pulposus extrusion (HNPE) or concurrent myelopathy. Characterization of HIZ lesions included several variable appearances in orientation and shape. HIZ lesions were most easily identifiable in the sagittal plane. Similar to humans, the most common site of HIZ without extrusion was the lumbosacral (LS) region. All the dogs with HIZ lesions as the most significant MRI finding, exhibited spinal pain and/or chronic paresis/plegia.Conclusions and clinical significanceBy introducing and defining HIZ lesions to the veterinary imaging nomenclature, we hope future studies will further examine the prevalence and clinical significance of HIZ lesions in canine patients.